2001
DOI: 10.1172/jci11427
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory functions of self-restricted MHC class II allopeptide-specific Th2 clones in vivo

Abstract: We studied T-cell clones generated from grafts of rejecting and tolerant animals and investigated the regulatory function of Th2 clones in vitro and in vivo. To prevent allograft rejection, we treated LEW strain recipient rats of WF strain kidney grafts with CTLA4Ig to block CD28-B7 costimulation. We then isolated epitope-specific T-cell clones from the engrafted tissue, using a donor-derived immunodominant class II MHC allopeptide presented by recipient antigen-presenting cells. Acutely rejected tissue from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 41 publications
4
52
0
6
Order By: Relevance
“…One could speculate that the Th2 switch observed in the graft and periphery of CCR5-deficient animals may be protective against islet allograft destruction. However, a regulatory function of Th2 cells in alloimmune responses remains controversial (25)(26)(27)). Animals lacking the Th2 cytokine IL-4 can accept allografts (28), although this is not a universal finding in all models (29).…”
Section: Grafts From Ccr5mentioning
confidence: 99%
“…One could speculate that the Th2 switch observed in the graft and periphery of CCR5-deficient animals may be protective against islet allograft destruction. However, a regulatory function of Th2 cells in alloimmune responses remains controversial (25)(26)(27)). Animals lacking the Th2 cytokine IL-4 can accept allografts (28), although this is not a universal finding in all models (29).…”
Section: Grafts From Ccr5mentioning
confidence: 99%
“…immune regulation | MHC class II T he allogeneic response to organ transplantation was initially considered to be predominantly mediated by the Th1 population whereas the Th2 population was believed to oppose Th1 cell activation, thus favoring graft survival (1). Recent studies have identified additional CD4 + T cell subsets including IL-17-producing CD4 + T cells (Th17) and CD4 + FoxP3 + regulatory T cells (Tregs) (2).…”
mentioning
confidence: 99%
“…In the supernatants of these cultures, TNF-␣, IFN-␥, and IL-2 were detectable in this strain combination (LEW into WF.1L). Interestingly, in the reversed strain combination, in which no significant signs of chronic rejection were observed, IL-4 and IL-10 were detectable not only in the culture supernatants but also in the kidney grafts of those animals, reflecting type 2 cytokine expression, previously associated with transplantation tolerance (30). It has been speculated that Th2 responses may be responsible for the development of chronic rejection (31); in contrast, we found that chronic rejection was associated with a Th1 response, in keeping with human studies that have shown that alloreactive T cells cloned from chronically rejecting patients were universally of the Th1 phenotype (32).…”
Section: Discussionmentioning
confidence: 80%